That depends on the value of x and y. As an expression, "x + y" can't be simplified.
6x - y
2(x+y) is twice the sum of x and y, and 2x+y is the sum of twice x and y
x+y
(x + y)(x + y)(x + y)
5(x^2 + y)
6x - y
Twice the sum of 'x' and 'y' . . . 2(x+y) The sum of twice 'x' and 'y' . . . (2x+y)
2(x+y) is twice the sum of x and y, and 2x+y is the sum of twice x and y
Sum Numb!
When 'x' and 'y' both have the same sign.
The sum of x and y decreased by their product is (x + y)- xy.
x+y
X+y
(x + y)(x + y)(x + y)
5(x^2 + y)
Suppose the numbers are x and y. The sum of their reciprocals = 1/x + 1/y = y/xy + x/xy = (y+x)/xy = (x+y)/xy = 10/30 = 1/3
The answer to Y x plus 5 Y 6 is Y(x+5Y5).One possible solution to y x plus 5 y 6 is Y(x+5Y5).